Fishermen do more than fish: local ecological knowledge of raftsmen about the arboreal species used to construct rafts (Bahia, Brazil) - Isis Leite Medeiros Mascarenhas Andrade; Marcelo Schramm Mielke; Nivaldo Peroni; Alexandre Schiavetti (BMC, 2018)
Abstract Background Traditional raft (jangada), piúba wood raft (jangada de pau de piúba), six-log raft (jangada de seis paus), and wooden raft (jangada de pau) are some of the names given to the traditional Brazilian watercrafts created from the buoyancy of bound logs. The traditional raft is a watercraft used and built by artisan fishermen who have, throughout generations, kept and improved knowledge related to this practice and the use of the plant species they need as raw materials. Active groups of these fishermen and their watercrafts are distributed along 200 km of the coast of the state of Bahia. The fishermen interviewed in this study are at the southern limit of distribution for the use of this type of vessel. Methods This study aimed to characterize the use of the arboreal species applied in the construction of the traditional raft in the municipalities of Uruçuca, Ilhéus, and Canavieiras in the southern State of Bahia, Brazil. For this purpose, structured and semi-structured interviews were individually conducted with 36 fishermen, and walking tours were conducted with specialists in the construction of the watercraft. Results We observed that the raftsmen use 21 species to construct the traditional raft. The features of the wood, such as density, flexibility, and availability, are the main criteria applied to choose the arboreal species. Some species are preferred, such as pau de jangada (Apeiba tibourbou ) and biriba (Eschweilera ovata), which are the most frequently employed in watercraft manufacturing. Conclusions The southern Bahia population is familiar with the different tree species that are linked to their fishing activities. The main link between the fishermen and the useful species is present in the practice of raft construction. Currently, the restricted access to raw materials limits this practice, which consequently results in the cultural erosion of this community.